Efeito da ordem dos exercícios sobre o desempenho durante uma sessão de treinamento resistido no método circuito - André Luiz Torres Pirauá; Natália Barros Beltrão; Dalton Roberto Alves Araújo de Lima Júnior; Gregório Reis de Queiroz; Jefferson Gomes de Souza; Bruno Machado Melo; Rodrigo Cappato de Araújo (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to compare total work volume, number of repeti-tions and rate of perceived effort performed in two different sequences of circuit training sessions. Eleven recreationally trained men (24.0 ± 4.8 years, 76.1 ± 8.5 kg, 1.75 ± 0.06 m) performed two different sequences of circuit training sessions. All sessions consisted of eight stations (exercises) of three sets in circuit, performed to volitional fatigue, alternating upper and lower body exercises, with 1-minute rest interval between exercises. Sequence A began with multiple joint exercises and progressed to single joint exercises, whereas sequence B was performed with the opposite exercise order. Number of repetitions and rating of perceived exertion (RPE) were compared by repeated measures multivariate analysis of variance (repeated measures MANOVA). Total work volume (TWV) was compared by paired t-test. There were no differences between exercise order for TWV (p=0.47) and RPE of all exercises (p>0.05). For both sequences, number of repetitions was greater when exercise was performed first (p<0.05). These results indicate that during a circuit training session, exercises order influenced the number of repetition, but did not influence TWV and RPE. These findings may suggest that for those who aim overall muscular gains, similar results will be obtained with single and multiple joint, upper and lower body circuit training exercise orders. Similarly, exercise intensity will be similarly perceived regardless of exercise sequences. For those who aim specific muscle group gains, priority exercises must be performed first.